Supporting information visualization through topic maps - Marcos, Adérito (2011)
We are living a phenomenon of accelerated information production with different accessing sources. Hence users are faced with a growing problem: accessing (navigation) and filtering specific information contained in large datasets, which are increasing in size. Procedures such as data filtering and gathering are now simplified through a new concept known as Topic Maps. The application of Virtual Reality technologies enables to present and interact with multidimensional information in a 3D space. In this paper we present INSPHERE, a new visual metaphor for information visualization,based on both, Virtual Reality techniques, and “geographical information maps” provided by Topic Maps.